The Bristol CMIP6 Data Hackathon. (25th February 2022) - Mitchell, Dann M.; Stone, Emma J.; Andrews, Oliver D.; Bamber, Jonathan L.; Bingham, Rory J.; Browse, Jo; Henry, Matthew; MacLeod, David M.; Morten, Joanne M.; Sauter, Christoph A.; Smith, Christopher J.; Thomas, James; et al.
Abstract : The Bristol CMIP6 Data Hackathon formed part of the Met Office Climate Data Challenge Hackathon series during 2021, bringing together around 100 UK early career researchers from a wide range of environmental disciplines. The purpose was to interrogate the under‐utilised but currently most advanced climate model inter‐comparison project datasets to develop new research ideas, create new networks and outreach opportunities in the lead up to COP26. Experts in different science fields, supported by a core team of scientists and data specialists at Bristol, had the unique opportunity to explore together interdisciplinary environmental topics summarised in this article.